PKI’s stigmatization after 1965 in the Installation of Artwork - Muhammad Bagus Ramadhan (Institut Seni Indonesia Padang Panjang, 2020)
The Lamongan people, since 1965 after the G30S PKI became the basis for the escape of the PKI’s lackeys who infiltrated the confusion of farming community in Lamongan. Since then, BTI (Barisan Tani Indonesia) has emerged among the peasant community, although it cannot be flat that the Lamongan community is a BTI community. From the basis of the event, the writer wants to voice through visualizing ideas and ideas into the creation of installation art works, which was given the title Stigmatization of the PKI after 1965 in the Creation of Installation Artworks. The installation is visualized using a light base that produces shadows. The writer wants to convey a condition in which the general public who never knew the other side of the history that was released by the government, The writer wanted to make the installation as a medium for sound and a new space for thinking in seeing the dark historical context of the G30 S PKI. This event became a foothold in the formation of the ideology of the writer creating artworks. This installation of art is realized using David Campbell’s method approach; 1. Preparation, 2. Concentration, 3. Incubation, 4. Illumination, 5. Verivication.